2022
DOI: 10.1002/cite.202100145
|View full text |Cite
|
Sign up to set email alerts
|

Bubble Cutting by Cylinder – Elimination of Wettability Effects by a Separating Liquid Film

Abstract: Dedicated to Prof. Dr. Thomas Hirth on the occasion of his 60th birthdayExperiments and simulations are presented for the interaction of single bubbles rising in a viscous liquid against a horizontal cylinder (Ø = 4 mm) of varying wettability. The slide-off of small and the cutting of larger bubbles into two daughter bubbles observed in the experiment are reproduced by phase-field simulations. It is shown that in the entire process bubble and cylinder are separated by a liquid film, which eliminates any influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…In dimensionless terms, this could be summarized as larger bubbles with Eo > 4 being able to pass through, while smaller bubbles ( Eo < 4) are able to pass only when the mesh spacing is larger than 0.625 times the bubble diameter. A liquid film between the bubble and wire was observed by Wang et al upon performing DNS simulations of two bubbles of different volumes impacting a cylindrical wire. As a result, it can be maintained that bubble–wire interaction is independent of surface wettability effects, thus simplifying our study.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…In dimensionless terms, this could be summarized as larger bubbles with Eo > 4 being able to pass through, while smaller bubbles ( Eo < 4) are able to pass only when the mesh spacing is larger than 0.625 times the bubble diameter. A liquid film between the bubble and wire was observed by Wang et al upon performing DNS simulations of two bubbles of different volumes impacting a cylindrical wire. As a result, it can be maintained that bubble–wire interaction is independent of surface wettability effects, thus simplifying our study.…”
Section: Introductionmentioning
confidence: 87%
“…23 Wire−Bubble Interactions. Wang et al 15 had remarked that the bubbles maintain a certain distance from the wires via a thin liquid film. Thus, the bubbles sense the wires indirectly.…”
Section: ■ Numerical Frameworkmentioning
confidence: 99%
“…The bubble experiences multiple contact zones when it touches the mesh depending on the scenario. Wang et al 14 observed through DNS studies that the presence of the liquid film that separates the gas from the cylinder surface effectively eliminates the influence of surface wettability on the bubble cutting process. Parts of the bubble that do not experience pressure force from the mesh are kept together with the help of surface tension.…”
Section: Interactionmentioning
confidence: 99%
“…It was observed that larger bubbles (Eo > 4) could pass through, while smaller bubbles (Eo < 4) could only pass when the mesh spacing s was less than 0.625 times the bubble diameter. Wang et al 14 performed DNS simulations of two bubbles of different volumes impacting a cylindrical wire and observed that the bubbles do not come in direct contact with the cylinder. Instead, a separating liquid film is formed which eliminates any effect of surface wettability.…”
Section: ■ Introductionmentioning
confidence: 99%